Alternatif Perencanaan Penanggulangan Longsoran Menggunakan Dinding Penahan Tanah Type Cantilever Pada Ruas Jalan Toboli – Kebun Kopi Sulawesi Tengah - Natasia, Icha; Nurdin, Abdul Rahim; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
According to ESDM, 215 ground motion events were reported during 2023. Landslides are natural phenomena that occur frequently and have a significant impact. Landslides also occur in road construction, such as the landslide on the Toboli - Kebun Kopi road section. There are two methods of dealing with landslides, namely preventive methods and curative methods. Preventive method is a method used to prevent landslides, while curative method is a method used to handle landslides that have occurred. On the Toboli - Kebun Kopi road section, landslides have occurred, therefore the countermeasure uses curative methods, one of which is a cantilever type retaining wall. The purpose of this research is to obtain the stability value of slope structure, and predict whether deformation occurs after countermeasures are taken. Based on the results of the analysis, the structural stability value is bolster: 2.850 > 2 (safe), shear: 2.268 > 1.5 (safe) and soil bearing capacity: 106 > 3 (safe). And the stability of slope after being given countermeasures using the finite element method with help of the plaxis program on saturated slopes: 1.60 and unsaturated slopes: 1.90. After given countermeasures deformation occurs on saturated slopes by 3.59 cm and unsaturated by 3.42 cm.